Proceso de atención de enfermería en recién nacido con hiperbilirrubinemia - Gómez Banchén, Luis Javier (2018)
This case study aims to analyze the standards, care and nursing loaves that should be taken in hospitals throughout the equator, for which deductive and exploratory method was used to determine its application. Abstract After being born, the baby goes through a period of transition of physiological changes and adjustments. During this period, the newly born can experience neonatal jaundice, an imbalance characterized by the yellow pigmentation of the skin as the result of the high levels of circulating bilirubin. This problem is one of the main causes of both on-term and pre-term neonatal mortality. There are different maternal and neonatal risk factors involved in the issue and, although its mortality rates are low, a delay in diagnosing and treating neonatal jaundice leads to severe complications such as kernicterus. A hyperbilirubinemia due to blood incompatibility between the mother and the baby, like in this particular case, requires immediate attention from the neonatal-care nursing professional in order to limit the damage, and to favor a prompt recovery, the reunion of the mother and her baby, and the integration of the baby into other family dynamics. This study was conducted within the conceptual frame of the Roy’s Adaptation Model and through the nursing process. Although, a considerable decrease in the bilirubin level was not achieved, the obtained results were considered satisfactory since the level of physiological adaptation of the newborn improved significantly.